Telephone Referral to a Paediatric Emergency Department: Why Do Parents Not Show Up? - Mélanie Freiermuth; Christopher J. Newman; Judit Villoslada (Children, 2023)
Medical call centres can evaluate and refer patients to an emergency department (ED), a physician or provide guidance for self-care. Our aim was (1) to determine parental adherence to an ED orientation after being referred by the nurses of a call centre, (2) to observe how adherence varies according to children’s characteristics and (3) to assess parents’ reasons for non-adherence. This was a prospective cohort study set in the Lausanne agglomeration, Switzerland. From 1 February to 5 March 2022, paediatric calls (<16 years old) with an ED orientation were selected. Life-threatening emergencies were excluded. Parental adherence was then verified in the ED. All parents were contacted by telephone to respond to a questionnaire regarding their call. Parental adherence to the ED orientation was 75%. Adherence decreased significantly with increasing distance between the place the call originated and the ED. The child’s age, sex and health complaints within calls had no effect on adherence. The three major reasons for non-adherence to telephone referral were: improvement in the child’s condition (50.7%), parents’ decision to go elsewhere (18.3%) and an appointment with a paediatrician (15.5%). Our results offer new perspectives to optimise the telephone assessment of paediatric patients and decrease barriers to adherence.